The theoretical aspect of the image formation and socialization of future pre-school teachers - Sopovа, Dana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article under consideration deals with the concept of the "image", emphasizes the pedagogical aspects of image formation and socialization of future specialist of the pre-school institutions.
Keywords: socialization; image; professional and pedagogical image; teacher; educator; personality; preschool institution; student-centered learning